If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2S + -6) = 9 Reorder the terms: 3(-6 + 2S) = 9 (-6 * 3 + 2S * 3) = 9 (-18 + 6S) = 9 Solving -18 + 6S = 9 Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 6S = 9 + 18 Combine like terms: -18 + 18 = 0 0 + 6S = 9 + 18 6S = 9 + 18 Combine like terms: 9 + 18 = 27 6S = 27 Divide each side by '6'. S = 4.5 Simplifying S = 4.5
| x(x-y)-y(y-x)= | | x-17=12.99 | | x-.3x=1000 | | 9(x)+50=3(x)-22 | | 20b^2-156b-32= | | 9(x)+14=6(x)-13 | | -1.4(x)-2=-0.9(x)+5 | | -1.4x(x)-2=-0.9(x)+5 | | 3w-9w=18 | | 17=25+3x | | -7x+1+8x=-1+20 | | (3x^8)(-4x^4)(5x^8)=y | | 7(x-2)+8=7x-3 | | -2(3x+8)=3-6x | | 5(-3X-10)-(x+3)=4(4x+5)+13 | | (6t^3+2t)-(-2t^3-7t+4)= | | h(x)=x^3+8x-5 | | -12=2(w-7)-4w | | -3(4s-6)-18=-3(9s+2)-3 | | 7+8v+v^2=0 | | 53=4t-7 | | (5x+1)+(7x-23)=180 | | -4(5y-7)+3(4y+5)= | | 4sin^2(x)+4sinx+1=0 | | 0.31t-t/6=1 | | 23x+32=12x-7 | | 6x^2+3x-2k(x^2+x+1)-2=0 | | -4x-.5=15.5 | | -4-.5=15.5 | | 35=-1/3x+5 | | 35=-.33x+5 | | 35=-33x+5 |